Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Northern Mozambique at a Crossroads, 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

The Evidence Is In: How Should Youth Employment Programs In Low-Income Countries Be Designed? - Fox, Louise; Kaul, Upaasna (Policy Research Working Papers, 2018)
Youth in many low-income countries are entering the labor force in unprecedented numbers, yet many struggle to secure rewarding livelihoods. This paper outlines the economic development challenges that constrain youth's transition into employment, and it parses the evidence on which programs and policies appear to speed that transition. It concludes that it may be time for a fundamental reassessment of approaches for addressing youth employment and the youth transition in low-income countries. Employment opportunities in low-income countries reflect the pace of economic and structural transformation. In designing strategies, policies, and programs to meet the entry-into-employment challenge for youth, the starting point is to diagnose the economy and current/future employment opportunities. Combined with the analysis of youth employment problems from a structural transformation perspective, evidence from rigorous evaluations of youth employment interventions provides new insight into which kinds of interventions are more likely to help youth succeed in certain contexts. The evidence reviewed here casts serious doubt on the efficacy and value of training interventions to help youth enter formal wage employment. The case is stronger for interventions that speed the transition to self-employment in farming or non-farm household enterprises. Support for development of transferable character skills and social integration among youth through positive youth development programs should be tested further for employment and earnings impacts, perhaps along with cash transfers to youth or access to finance. In reviewing the evidence on the cost-effectiveness and sustainability of youth employment impacts, the paper also notes the need for better measures of displacement and general equilibrium effects.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; employment / emprego; youth / juventude

Youth Social Exclusion and Lessons from Youth Work: Evidence from literature and surveys - Paolini, Giulia; Brel, Patrice; Vanandruel, Colette (European Commission Education, Audiovisual and Culture Executive Agency (EACEA), 2013)
It is widely recognised that social exclusion produces deep and long-term damage to the living conditions, social and economic participation, emotional life, and health status of young people. It also contributes to the intergenerational transmission of poverty. In turn, insecurity in living standards, political and social isolation, feelings of estrangement and unhealthy lifestyles aggravate pre-existing conditions of social exclusion. This results in a vicious circle where socially excluded young people are in even more danger of suffering from additional material deprivation, social and emotional marginalisation, and health issues, which in turn expose them to more serious risks of exclusion. Almost one out of three young persons between the ages of 18 and 24 is at risk of poverty or social exclusion in the European Union. Youth work can offer opportunities for preventing and remedying this vicious circle. By offering young people targeted support, opportunities for non-formal learning, information on health and wellbeing, and opportunities for positive integration into the local community, youth workers are able to reduce the risks of further social exclusion linked to deteriorating living conditions and unhealthy life styles. The EU Youth Strategy recognises the relevance of youth work to mitigating the effects of social exclusion amongst young people. Reaffirming this concept, the Council Resolution on Youth Work of 2010 invited Member States and the Commission to support the development of youth work at local, regional, national and European level. The relation between youth work and social inclusion also touches upon the priorities established by the 2012 EU Youth Report. A general overview of the fundamental threats to social inclusion experienced by young people can be found in the dedicated chapter of the Youth Report. The benefits coming from youth work to the inclusion of young people, and in particular of those with a migrant background, has been recognised in the Conclusions of the Council of 27 November 2012. To address the risks of exclusion run by many young individuals, the Social Investment Package adopted by the European Commission seeks to improve the situation of young people by tackling childhood disadvantage, improving access to quality education and support services, helping young people develop skills relevant to the labour market, and ensuring work experience and on-the-job training and helping young people find a first good job (European Commission, 2013a). This paper aims at offering evidence about the situation of social exclusion suffered by young people in the European Union, and the positive effects that youth work initiatives produce in fostering their (re)inclusion. Looking at factual information on the main conditions of exclusion is essential to have an accurate understanding of the threats encountered by young people. Available data and research literature illustrate the major reasons behind the marginalisation of young Europeans, and pave the way to the development of effective policy strategies to prevent it.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Youth exclusion, violence, conflict and fragile states - Hilker, Lyndsay McLean; Fraser, Erika (Social Development Direct, 2009)
This report forms part of a portfolio of work on youth focussed on two interconnected thematic areas: youth, jobs and growth and on youth exclusion, fragile states and conflict and complements work being conducted to develop a Youth Participation Guide for DFID staff. It is intended to inform a DFID Policy Briefing and a practical Guidance Note on addressing youth exclusion and unemployment. The objectives of the study are: (i) To scope out existing evidence and analysis on the links between youth exclusion, violence, conflict and fragile states and distil this information to enable DFID (and partners) to better understand the implications for poverty elimination, state and community-building, peace-building, Disarmament, Demobilisation and Reintegration (DDR) and conflict prevention, in order to address the issues more effectively in policy and programmes; (ii) To develop a conceptual framework that renders this information manageable while still reflecting the many dimensions of this issue. The study involved a desk-based literature review and consultations with a small number of key informants from DFID, other donors, academia and youth groups. This study focuses mainly on people aged 15-24, but conceptualises “youth” as a transitional stage in life between childhood and adulthood rather than as a rigid construct based on age. It recognises the diversity of youth by gender, class, ethnicity and focuses on the multiple dimensions of exclusion that systematically disadvantage youth. It also takes a holistic approach to violence – recognising that in practice different forms of violence (e.g. political, criminal, interpersonal, extremism) may overlap and that some of the same structural and proximate factors may drive youth engagement in different forms of violence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude